Educação profissional e território: determinações sócio-históricas presentes no Vale do Paraíba - SP - Esteves, Thaís Ribeiro (2018)
The theme of this dissertation is about professional education and territory. In order to understand the multiple determinations of the professional education policy in Vale do Paraíba – São Paulo, in the setting up context of the Federal Institute of Education, Science and Technology of São Paulo, we seek, based on Lefebvre’s theoretical and methodological framework, to historically date the existing social relations in this region, as well as the paths of the Brazilian professional education, aspiring an analysis of the present time. We understand that the temporal (mis)matching is an integral part of the dynamics of urbanization present in this space, with repercussions on the professional education policies. Through bibliographic analysis and participant observation, socio-historical research into Vale do Paraíba was carried out, which included the apprehension of political, economic and cultural determinations. Our analysis is mainly focused on two cities: São José dos Campos and Jacareí – municipal centers of economic importance for the region and where the Federal Institute units were set up at the beginning of the 21st century. This inquiry is underlain by the notion that Brazil is a country of unfinished modernity (MARTINS, 2015), where there is a striking mismatch between the economic and the social. Given our participation in the Double Diploma Program – an agreement between the Pontifical Catholic University of São Paulo and Grenoble Alpes-France University, this dissertation also contemplates elements of our approach to the French reality, with regard to professional training policy in its territorial relation, in the Department of Isère